Types of Responses of the EU Labour Markets in the Early Covid-Pandemic Period - Cicha-Nazarczuk, Marlena (Olsztyn Economic Journal, 2023)
The dual impact of the COVID-19 pandemic (simultaneous demand and supply shocks) was manifested by values of the economically important indicators, including measures applied to the labour market. The magnitude and scope of the response on the European Union labour markets were significantly country-specific parameters. The purpose of this article is to identify the types of responses of the EU labour markets in the early phase of the COVID-19 pandemic. One of the agglomeration clustering methods, namely the Ward approach, has been applied to create groups of the studied labour markets. The application of this method led to the identification of 4 clusters of economies, characterized by different types of response in terms of the direction and intensity of changes on the labour market during the COVID-19 pandemic.